Characterization of a New Multifunctional GH20 β-N-Acetylglucosaminidase From Chitinibacter sp. GC72 and Its Application in Converting Chitin Into N-Acetyl Glucosamine - Chen, Yan; Zhou, Ning; Chen, Xueman; Wei, Guoguang; Zhang, Alei; Chen, Kequan; Ouyang, Pingkai (Frontiers in Microbiology, 2022)
In this study, a gene encoding β-N-acetylglucosaminidase, designated NAGaseA, was cloned from Chitinibacter sp. GC72 and subsequently functional expressed in Escherichia coli BL21 (DE3). NAGaseA contains a glycoside hydrolase family 20 catalytic domain that shows low identity with the corresponding domain of the well-characterized NAGases. The recombinant NAGaseA had a molecular mass of 92 kDa. Biochemical characterization of the purified NAGaseA revealed that the optimal reaction condition was at 40 °C and pH 6.5, and exhibited great pH stability in the range of pH 6.5–9.5. The Vmax, Km, kcat, and kcat/Km of NAGaseA toward p-nitrophenyl-N-acetyl glucosaminide (pNP-GlcNAc) were 3333.33 μmol min-1 L-1, 39.99 μmol L-1, 4667.07 s-1, and 116.71 mL μmol -1 s-1, respectively. Analysis of the hydrolysis products of N-acetyl chitinoligosaccharides (N-Acetyl COSs) indicated that NAGaseA was capable of converting N-Acetyl COSs ((GlcNAc)2–(GlcNAc)6) into GlcNAc with hydrolysis ability order: (GlcNAc)2 > (GlcNAc)3 > (GlcNAc)4 > (GlcNAc)5 > (GlcNAc)6. Moreover, NAGaseA could generate (GlcNAc)3–(GlcNAc)6 from (GlcNAc)2–(GlcNAc)5, respectively. These results showed that NAGaseA is a multi-functional NAGase with transglycosylation activity. In addition, significantly synergistic action was observed between NAGaseA and other sources of chitinases during hydrolysis of colloid chitin. Finally, 0.759 g/L, 0.481 g/L and 0.986 g/L of GlcNAc with purity of 96% were obtained using three different chitinase combinations, which were 1.61-, 2.36-, and 2.69- fold that of the GlcNAc production using the single chitinase. This observation indicated that NAGaseA could be a potential candidate enzyme in commercial GlcNAc production.